Case report: Pneumocystis jirovecii pneumonia in a severe case of Aicardi–Goutières syndrome with an IFIH1 gain-of-function mutation mimicking combined immunodeficiency - Železnik, Mojca; Soltirovska Šalamon, Aneta; Debeljak, Maruša; Goropevšek, Aleš; Šuštar, Nataša; Ključevšek, Damjana; Ihan, Alojz; Avčin, Tadej (Frontiers in Immunology, 2023)
Aicardi-Goutières syndrome (AGS) is a genetically determined early-onset progressive encephalopathy caused by mutations leading to overexpression of type I interferon (IFN) and resulting in various clinical phenotypes. Gain-of-function (GOF) mutation in the IFIH1 gene is associated with robust production of type I IFN and activation of the Janus kinase (JAK) – a signal transducer and activator of the transcription (STAT) pathway and is causing AGS type 7. We detail the clinical case of an infant who initially presented Pneumocystis jirovecii pneumonia (PCP), had recurrent respiratory infections, and was later treated with a JAK inhibitor, baricitinib, because of a genetically confirmed GOF in the IFIH1 gene. This spectrum of IFIH1 GOF mutations with overlapping features of hyperinflammation and severe opportunistic infection has not been described before, and it mimics combined immunodeficiency (CID). In our case, therapy with baricitinib effectively blocked IFN-α activation and reduced STAT1 signaling but had no effect on the progression of the neurological disease.